A study on comparison of conventional suturing and tissue adhesive (2-octyl cyanoacrylate) for skin closure in inguinal hernia surgeries - Swaminathan, Shanthi Ponnandai; Jebasingh, Arun Victor; Annadurai, Anbuselvi; Mannan, Mannar (International Surgery Journal, 2018)
Background: Wound closure techniques have evolved from suture material to advanced techniques that include skin staplers, skin glue and adhesive tapes. Based on efficacy of advanced suturing techniques patient may be benefited with better cosmesis, lesser postoperative pain, less wound infection and lesser hospital stay. The aim of the study was to compare the results of adhesive glue with suture material in skin closure in hernia surgeries. Methods: This study involves 100 patients undergoing open inguinal hernia surgery. In 50 of the patient’s skin closure was done with conventional suturing (3-0 ETHILON) and other 50 patients with tissue glue (2-octyl cyanoacrylate). Observation regarding postoperative pain, skin closure time and scar assessment were made, and their results were compared. Results: The mean time taken for skin closure in adhesive group was 2.72±1.32minutes and that of suture group was 4.88±1.533minutes. This difference was of great significance with p value of <0.001. The visual analogue scale shows mean value of 5.3±0.68 for suture group and for skin group it was 3.68±0.62. This value was of great significance with p value <0.001. Postoperative pain was comparatively less in tissue glue group. Postoperative scar was analysed with Vancouver scar scale at regular intervals. The mean score for suture group was 8.3±0.8 and for skin glue group it was 2.8±0.75. These differences of score was of great significance with p value <0.001. Conclusions: Adhesive glue is superior to conventional suturing in clean elective surgeries. It is a safe and an effective method of skin closure with less postoperative pain and better cosmesis of the scar.